Genomic insights into the mitochondria of 11 eastern North American species of Cladonia. Issue 2 (3rd July 2018) - Brigham, Laurel M.; Allende, Luis M.; Shipley, Benjamin R.; Boyd, Kayla C.; Higgins, Tanya J.; Kelly, Nicholas; Anderson Stewart, Carly R.; Keepers, Kyle G.; Pogoda, Cloe S.; Lendemer, James C.; Tripp, Erin A.; Kane, Nolan C.
Abstract: Cladonia is among the most species-rich genera of lichens globally. Species in this lineage, commonly referred to as reindeer lichens, are ecologically important in numerous regions worldwide. In some locations, species of Cladonia can comprise the dominant groundcover, and are a major food source for caribou and other mammals. Additionally, many species are known to produce substances with antimicrobial properties or other characteristics with potentially important medical applications. This exceptional morphological and ecological variation contrasts sharply with the limited molecular divergence often observed among species. As a new resource to facilitate ongoing and future studies of these important species, we analyse here the sequences of 11 Cladonia mitochondrial genomes, including new mitochondrial genome assemblies and annotations representing nine species: C. apodocarpa, C. caroliniana, C. furcata, C. leporina, C. petrophila, C. peziziformis, C. robbinsii, C. stipitata, and C. subtenuis . These 11 genomes varied in size, intron content, and complement of tRNAs. Genes annotated within these mitochondrial genomes include 15 protein-coding genes, the large and small ribosomal subunits (mtLSU and mtSSU), and 23–26 tRNAs. All Cladonia mitochondrial genomes contained atp9, an important energy transport gene that has been lost evolutionarily in some lichen mycobiont mitochondria. Using a concatenated alignment of five mitochondrial genes ( nad2, nad4, cox1, cox2, and cox3 ), a Bayesian phylogeny of relationships among species was inferred and was consistent with previously published phylogenetic relationships, highlighting the utility of these regions in reconstructing phylogenetic history.